Understanding the Cisco ASA firewall : learning to install, configure, and manage Cisco firewalls and advanced VPN solutions - Larsson, Jimmy (O'Reilly, 2016)
"This is a best practices course on how to set-up, manage, and troubleshoot firewalls and VPNs using the Cisco ASA (Adaptive Security Appliance). Drawing on his 15 years of experience implementing Cisco firewalls, instructor Jimmy Larsson shows you the actual hands-on commands and configurations he uses in real life situations. The course is targeted at first time Cisco ASA users and those with some ASA experience looking to fill the gaps in their knowledge. Larsson recommends that learners have access to a Cisco firewall in order to practice the methods covered in the course."--Resource description page.